Recent Advances in the Development of Floating Microspheres for the Treatment of Gastric Ulcers - Radha Rani, Manish Kumar, Narendra Yadav, Shailendra Bhatt, Anuj Malik, Beena Kumari, Sangeeta, Dilshad, Anil Kumar (International Journal of Advanced Science and Technology, 2020)
Ulcers are lesions which is a discontinuity of gastrointestinal mucosa. A variety of medications are used to treat mild to reasonable ulcers. Drugs used to treat ulcers are called anti-ulcer drugs. Floating microspheres organized by solvent-evaporation method using polymers and solvents whose   particle size analysis, encapsulation efficiency, scanning electron microscopy and drug loading, in-vitro release study, stability studies characterization was carried out which showed an better absorption and bioavailability by retaining the system in abdomen  for a extended period of time. Large efforts have been made global to investigate these systems rendering to patient necessities, both in terms of compliance and therapeutic efficacy. Floating microspheres as gastro retentive dosage forms exactly manage the release rate of target drug to a particular site and enable a vast impact on physical condition. This review in brief 87klj emphasizes on Gastro Retentive Drug Delivery system of anti-ulcer drug. Special categories parallel to antacids, anti diabetic, antifungal and anticancer drugs are formulated into Floating. Drug Delivery System.  These systems also present fabulous openings in the designing of most recent controlled and delayed release oral formulations, thus extending the frontier of futuristic pharmaceutical enlargement. In the present review advantages, preparation methods and applications are discussed. Keywords: Floating microspheres, Solvent evaporation method, Ulcers.